Hubungan Pengetahuan Ibu Dengan Pemberian Vaksin Covid-19 Pada Anak Usia 6-11 Tahun Di SD Negeri 01 Sitiung Kabupaten Dharmasraya - Purwati, Rati; Khotimah, Siti; Sandra, Nurheliza Deli (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Vaccines are immunogenic biological products (causing an immune response) in the form of whole microorganisms or parts of harmless microorganisms. Coronavirus disease 2019 (COVID-19) is an illness caused by a new coronavirus called SARS-CoV-2. The World Health Organization (WHO) has carried out a program to achieve vaccination for every citizen in the world in which more than 300 million doses of the COVID-19 coronavirus vaccine have been given to 100 countries around the world. Graphic data on the Our World Data website as of August 21, 2021, shows that Indonesia is in fourth place with the largest population that has been vaccinated, namely 56.99 million people (31.21 million had two doses and 25.78 million only had one dose). The purpose of the study was to determine the relationship between knowledge and the administration of the covid-19 vaccine to children aged 6-11 years at SDN 01 Sitiung. This research method is accidental sampling, which is a sampling method by taking respondents who are or are available in a place according to the context. There were 22 respondents (68.8%) who had high knowledge, and 10 respondents (31.2%) had moderate knowledge and 32 children (100%) received the covid-19 vaccine. According to the results of the analytical test, there is no relationship between mother's knowledge and the administration of the Covid-19 vaccine to children aged 6-11 years at SDN 01 Sitiung. Because value(p equal to 0.969). So there is no relationship. Meanwhile, 19 respondents (59.4%) have positive knowledge and as many as 13 people (40.6%) have negative knowledge. According to the results of the analytical test, there is no relationship between the mother's attitude and the administration of the COVID-19 vaccine to children aged 6-11 years at SDN 01 Sitiung. Because the value ( p equal to 0.024). So no relationship. Conclusion: There is no significant relationship between Mother's Knowledge and with the administration of the covid-19 vaccine to children aged 6-11 at SDN 01 Sitiung. It is hoped that future researchers who conduct research with this title should use other methodologies.